Composite coating with light conversion and super-hydrophobic self-cleaning functions as well as preparation and application of composite coating
By using red light-emitting carbon dots and PDMS adhesive modified by green plants to prepare composite coatings, the problem of realizing the dual functions of light conversion and self-cleaning is solved, and the utilization rate of sunlight and material life is improved. It is suitable for agricultural greenhouses and buildings. Materials and solar cells.
Patent Information
- Application Number
- CN202310700752.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing technology is difficult to achieve a film structure with dual functions of light conversion and self-cleaning, and the concentration quenching of carbon dots limits its application. Dust and dirt on the surface of agricultural greenhouses, solar cells and building materials block the sun's light and reduce light. Able to utilize efficiency and material life.
Using green plants as raw materials and alcohol-soluble polymers to modify the red light-emitting carbon dot solution, combined with PDMS binder and hydrophobic white carbon black, a light-transformed coating is formed by lifting or coating, and a super-hydrophobic self-cleaning coating is sprayed. Form a composite coating to avoid energy transfer between carbon spots, improve solid phase luminescence performance, and ensure firm bonding of each layer through a semi-cured adhesive layer.
A composite coating with high light transmittance, superhydrophobicity and self-cleaning properties has been achieved, which improves the utilization rate of sunlight, extends the service life of the light-transmitting coating, maintains high light transmittance and mechanical stability, and is suitable for agriculture Greenhouses, building materials and solar cells.
Smart Images

Figure CN119119839A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional coatings and functional nanomaterial preparation, and more specifically, to a composite coating with light conversion, super-hydrophobic and self-cleaning functions, and its preparation and application. Background Art
[0002] Short-wave, high-energy ultraviolet light in solar radiation can cause damage, aging or degradation to animals, plants, plastics, rubber, etc., including humans. Therefore, it is usually necessary to shield ultraviolet light or convert it into long-wave, low-energy light. Among them, converting ultraviolet light into usable visible light through light conversion materials to improve the utilization rate of sunlight is an effective way to solve the ultraviolet light problem, which can be widely used in agriculture, building materials, solar cells and other fields.
[0003] In existing related reports, carbon dots can be used as light conversion materials to convert ultraviolet light into visible light, and are used in the preparation of light conversion films. However, due to the concentration quenching phenomenon of carbon dots, its application is severely limited. In addition, in practical applications, agricultural greenhouses, solar cells, and building materials are used outdoors for a long time, and the dust and dirt accumulated on the surface will block the penetration of sunlight, reduce the utilization of light energy, and seriously affect the use efficiency and life of various materials; while manual cleaning and maintenance are time-consuming, laborious, and costly. At present, there has been no report of a membrane structure that can achieve the dual functions of light conversion and self-cleaning. Based on this, in order to fill the scientific research gap and meet the application needs of today's society, it is urgent to develop a membrane structure that can achieve the dual functions of light conversion and self-cleaning. Summary of the invention
[0004] Based on the above defects, the first object of the present invention is to provide a method for preparing a composite coating with light conversion and super hydrophobic self-cleaning functions. The method first uses green plants as raw materials and alcohol-soluble polymers as modifiers to prepare a red light emitting carbon dot solution, which is then pulled or coated on various substrates to form a light conversion coating, and then uses an adhesion coating solution to form a semi-cured adhesion coating on the outside of the light conversion coating. When the adhesion coating is not completely cured and still has viscosity, a super hydrophobic self-cleaning coating formed by spraying a super hydrophobic self-cleaning coating solution is formed, and a composite coating is formed after complete curing.
[0005] The second object of the present invention is to provide a composite coating with light conversion and super hydrophobic self-cleaning functions prepared by the preparation method as described above. The composite coating has light wavelength conversion capability, high light transmittance, super hydrophobic self-cleaning capability, good light conversion anti-attenuation and self-cleaning stability, and the sprayed polydimethylsiloxane and hydrophobic white carbon black are firmly adhered to the adhesive coating after curing, and the adhesive coating is also firmly cured with the inner light conversion coating, which not only ensures the light transmittance and super hydrophobic stability of the composite coating, but also achieves the effect that each layer is not easy to separate.
[0006] The third object of the present invention is to provide an application of the composite coating as described above in the preparation of agricultural greenhouses, building materials, and solar cells.
[0007] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0008] The present invention discloses a method for preparing a composite coating with light conversion and super-hydrophobic self-cleaning functions, comprising the following steps:
[0009] 1) Prepare the light-converting coating solution
[0010] The green plants are washed and ground, extracted with ethanol at room temperature, an alcohol-soluble polymer is added to the extract and ultrasonic treatment is performed to obtain a mixed raw material solution;
[0011] The mixed raw material solution is transferred to a high-pressure reactor, and the reaction is carried out at 120-200°C for 2-24 hours. After the reaction is completed, the mixture is centrifuged, and the supernatant is collected and refrigerated at 0-5°C for later use;
[0012] 2) Preparation of adhesive coating solution
[0013] dispersing the PDMS adhesive in a diluent to obtain an adhesion coating solution;
[0014] 3) Preparation of super hydrophobic self-cleaning coating solution
[0015] Dispersing PDMS adhesive and hydrophobic silica in a diluent to obtain a super hydrophobic self-cleaning coating solution;
[0016] 4) Preparation of light-converting coating
[0017] The pretreated substrate is immersed in a light conversion coating solution, pulled, and then dried at 40-60° C. for 0.5-2 h to obtain a light conversion coating;
[0018] Alternatively, the light conversion coating solution is coated on the pretreated substrate, and then dried at 40-60° C. for 0.5-2 h to obtain the light conversion coating;
[0019] 5) Preparation of semi-cured adhesive coating
[0020] The substrate with the light conversion coating is immersed in the adhesive coating solution, pulled, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating;
[0021] Alternatively, the adhesive coating solution is coated on the substrate having the light-converting coating, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating;
[0022] 6) Preparation of super hydrophobic self-cleaning coating
[0023] The super-hydrophobic self-cleaning coating solution is sprayed on the semi-cured adhesive coating, and cured to obtain a composite coating with light-converting and super-hydrophobic self-cleaning functions.
[0024] In the present invention, in order to solve the problems existing in the prior art, the inventor finally obtained a method for preparing a composite coating with light conversion, super hydrophobic self-cleaning function as described above through a large number of experimental attempts. The method is divided into two stages: the preparation stage of the coating liquid and the preparation stage of the composite coating. In the first stage, biomass such as green plants is selected as raw materials, modified with alcohol-soluble polymers, and a modified red light emitting carbon dot solution is obtained by solvent thermal method as a light conversion coating solution; the introduction of alcohol-soluble polymers can increase the steric hindrance on the surface of the carbon dots, effectively avoiding the non-radiative energy release caused by excessive energy transfer between carbon dot nanoparticles, and then realizing the solid-phase luminescence of carbon dots. Secondly, an adhesion coating solution is prepared with a PDMS adhesive, and a super hydrophobic self-cleaning coating solution is prepared with a PDMS adhesive and hydrophobic white carbon black to provide the system with hydrophobicity and self-cleaning ability. After each coating liquid is prepared, the composite coating is prepared. The light conversion coating can be prepared on the substrate by pulling or coating. The light conversion coating can provide the composite coating with light wavelength conversion capability, efficiently convert the ultraviolet light in sunlight into red light, improve the utilization rate of sunlight, and promote plant growth and development; the second layer of adhesive coating designed is also critical. A solution containing PDMS adhesive is selected for preparation. By mastering the curing characteristics of PDMS adhesives of different concentrations, the curing conditions are adjusted to form a semi-cured adhesive coating. The so-called semi-cured adhesive coating refers to a solution containing PDMS adhesive that loses fluidity as the diluent evaporates, but still maintains a certain viscosity. The formation of this intermediate coating can utilize the adhesion force that exists when it is not fully cured to firmly adhere the light conversion coating and the super hydrophobic self-cleaning coating. After complete curing, the three coatings are formed as one and are difficult to separate, which solves the problem of directly The super-hydrophobic self-cleaning coating formed on the light-converting coating is easy to fall off and separate. At the same time, the design of this intermediate coating is related to the preparation of the super-hydrophobic self-cleaning coating by spraying. Since the super-hydrophobic self-cleaning coating is formed directly by pulling or coating, there will be problems of weak adhesion and decreased transmittance. Therefore, the spraying method selected in this application is used to prepare the super-hydrophobic self-cleaning coating. After testing, the adhesive coating and the super-hydrophobic self-cleaning coating are interactively bonded after complete curing. The total thickness of the two coatings is about 20 microns, which has little effect on the transmittance. The super-hydrophobic self-cleaning coating formed by the third layer gives the composite coating excellent hydrophobicity and self-cleaning ability. The static water contact angle is up to 174°, and the rolling angle is less than 2°, which protects the integrity of the inner light-converting layer and improves the service life of the light-converting coating. At the same time, the self-cleaning performance can realize the removal of impurities such as dust and sand on the surface of the composite coating, maintaining a high light transmittance.
[0025] Further, the green plants include but are not limited to one or more of amaranth, spinach, chrysanthemum, bitter chrysanthemum, radish leaves, rapeseed, kale, fennel, lettuce, auricularia auricula, water spinach, shepherd's purse, celery, ginkgo leaves, cypress leaves, clover, purslane, foxtail grass, morning glory leaves and Stephania tatarinowii;
[0026] The alcohol-soluble polymer has good dispersibility and film-forming properties, and can effectively disperse the formed red light-emitting carbon dots. The alcohol-soluble polymer includes polyethylene glycol and / or polyvinyl pyrrolidone; exemplarily, the polyethylene glycol includes but is not limited to one or more of PEG-400, PEG-600, PEG-800, PEG-1000, PEG-1500, PEG-2000, PEG-3000 and PEG-4000, and the polyvinyl pyrrolidone includes but is not limited to one or more of PVP K15, PVP K30, PVP K60 and PVP K90.
[0027] Furthermore, the mass ratio of the green plants to the alcohol-soluble polymer is 10-20:1.
[0028] Furthermore, the concentration of the PDMS binder in the adhesion coating solution is 20-60 wt %.
[0029] Further, the PDMS adhesive is selected from DOWSIL (Dow Corning) SYLGARD 184PDMS. The commercially available DOWSIL (Dow Corning) SYLGARD 184PDMS is used according to a mass ratio of the main agent (PDMS) to the curing agent of 10:1. The main agent has a certain adhesion under the curing agent. By mastering the curing characteristics of PDMS adhesive solutions of different concentrations, the curing conditions are adjusted to form the semi-cured adhesive coating required by the present invention. According to a large number of experiments, when the concentration of the PDMS adhesive is 40wt%, it takes about 2h to fully cure at 60°C, and when the concentration of the PDMS adhesive is 50wt%, it takes about 1h to fully cure at 60°C.
[0030] Furthermore, the diluent includes, but is not limited to, one or more of n-hexane, petroleum ether, ethyl acetate and toluene.
[0031] Further, in the super hydrophobic self-cleaning coating solution, the mass ratio of the PDMS adhesive, the hydrophobic silica and the diluent is 0.02-0.2:0.01-0.1:1; exemplarily, the mass ratio of the PDMS adhesive, the hydrophobic silica and the diluent can be 0.02:0.01:1, 0.05:0.03:1, 0.1:0.01:1, 0.1:0.03:1, 0.1:0.05:1, 0.15:0.03:1, 0.15:0.05:1, 0.15:0.1:1, 0.2:0.05:1, 0.2:0.1:1, etc., or an interval formed by any two points thereof.
[0032] Further, the steps of pre-treating the substrate are:
[0033] The substrate is sequentially placed in water, ethanol and acetone solutions, ultrasonically cleaned for 10-30 minutes, then blown dry with high-purity nitrogen, and then cleaned with oxygen plasma for 3-10 minutes before use.
[0034] Further, the specific steps of the pulling process in step 4 are:
[0035] The pretreated substrate is placed in the light-converting coating solution, and after soaking for 10-90 seconds, it is pulled once at a rate of 0.5-5 mm / s, for a total of 1-20 times, and then dried at 40-60° C. for 0.5-2 hours to obtain a light-converting coating.
[0036] Further, the specific steps of the pulling process in step 5 are:
[0037] The substrate with the light-converting coating is immersed in the adhesive coating solution, and after each immersion for 10-90 seconds, it is pulled once at a rate of 0.5-5 mm / s, for a total of 1-20 times, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating.
[0038] Further, in step 6, the spraying pressure is 0.1-0.3 MPa, the spraying distance is 10-25 cm, and the spraying time is 3-15 s.
[0039] Furthermore, in step 6, the curing temperature is 50-60° C. and the curing time is 0.5-2 h.
[0040] Furthermore, the substrate includes but is not limited to plastic agricultural film, architectural glass or photovoltaic glass.
[0041] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0042] The present invention discloses a composite coating with light conversion, super-hydrophobic and self-cleaning functions, and the composite coating is prepared by the preparation method as described above;
[0043] Wherein, the composite coating comprises
[0044] Light conversion coating for converting the wavelength of ultraviolet light into red light;
[0045] A super hydrophobic self-cleaning coating for protecting the light-converting coating and maintaining the light-converting effect of the light-converting coating; and
[0046] An adhesive coating for adhering and fixing the light-converting coating and the super-hydrophobic self-cleaning layer.
[0047] In order to achieve the third object, the present invention adopts the following technical solutions:
[0048] The invention discloses an application of the composite coating as described above in the preparation of agricultural greenhouses, building materials and solar cells.
[0049] The beneficial effects of the present invention are as follows:
[0050] The present invention discloses a composite coating with light conversion, super-hydrophobic and self-cleaning functions, preparation and application thereof, which has the following advantages over the prior art:
[0051] 1. The present invention discloses for the first time a composite coating that can realize light conversion and super-hydrophobic self-cleaning functions, has excellent light conversion anti-attenuation, and still has a good light conversion effect after being soaked in water, subjected to high temperature and high humidity, and exposed to natural light. The composite coating is composed of a light conversion coating, an adhesion coating, and a super-hydrophobic self-cleaning coating. The light conversion coating can effectively absorb ultraviolet light in sunlight, convert ultraviolet light into red light, avoid damage to facilities and equipment caused by high-intensity ultraviolet light, and emit red light of ~670nm, with a fluorescence quantum yield of up to 17%, thereby realizing effective conversion of the incident spectrum; the adhesion ... and avoid damage to facilities and equipment caused by high-intensity ultraviolet light. Before the coating is cured, based on the adhesion of the PDMS adhesive, the sprayed superhydrophobic self-cleaning coating solution is effectively combined with the semi-cured PDMS coating, and the obtained superhydrophobic self-cleaning coating has good resistance to bending and 3M tape adhesion and peeling; the static water contact angle of the prepared superhydrophobic self-cleaning coating is up to 174°, and the rolling angle is less than 2°. Surface impurities such as dust and sand can be easily carried away by water, and it has good self-cleaning function. In addition, the superhydrophobic self-cleaning layer can effectively protect the light-converting coating, improve the service life of the light-converting coating, and does not affect the light transmittance of the substrate.
[0052] 2. When preparing the light-converting coating, the present invention selects a red-light emitting carbon dot made of green plants as raw materials and an alcohol-soluble polymer as a modifier. The introduction of the alcohol-soluble polymer can increase the steric hindrance on the surface of the carbon dot, effectively avoiding the non-radiative energy release caused by excessive energy transfer between carbon dot nanoparticles, thereby realizing the solid-phase luminescence of the carbon dot.
[0053] In summary, the composite coating with light conversion and super-hydrophobic self-cleaning functions prepared by the present invention has good light conversion and super-hydrophobic self-cleaning properties, and the composite coating has high light transmittance, high light conversion anti-attenuation and mechanical stability; the maximum temperature required for the preparation of the composite coating is 60°C, which can be met in an ordinary drying oven, and the drying time is short. Overall, the preparation method is simple, the equipment requirements are low, it is suitable for different substrates, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0055] Figure 1 Fluorescence excitation, emission spectrum and fluorescence quantum yield in solution of the spinach leaf-based red-light emitting carbon dots modified with polyethylene glycol PEG-1000 prepared in Example 1 when dispersed in ethanol solution and in solid state.
[0056] Figure 2 Fluorescence excitation, emission spectrum and fluorescence quantum yield in solution of the Amaranth leaf-based red light-emitting carbon dots modified with polyvinyl pyrrolidone (PVP) K30 prepared in Example 2 when dispersed in an ethanol solution and in a solid state.
[0057] Figure 3 It is a comparison of the light transmittance of the sample prepared in Example 5 and the original polyethylene film; the insets are digital photos and photos under 365nm ultraviolet irradiation of the original polyethylene film and the polyethylene film with the composite coating, respectively.
[0058] Figure 4 The cross-sectional layer structure of the sample prepared in Example 5 and the rough structure of the composite coating surface tested by a scanning electron microscope S-4800;
[0059] in, Figure 4 a in the figure is the cross-sectional layer structure of the polyethylene film with composite coating. Figure 4 Figure b is a rough structure diagram of the composite coating surface.
[0060] Figure 5 Fluorescence excitation and emission spectra of the sample prepared in Example 5.
[0061] Figure 6 Comparison of solar radiation intensity of the original polyethylene film and the sample prepared in Example 5.
[0062] Figure 7 The water contact angle and sliding angle of the sample prepared in Example 5;
[0063] in, Figure 7 a is the water contact angle, Figure 7 b is the rolling angle.
[0064] Figure 8 The water contact angle of the sample prepared in Example 5 before and after 1000 bending and curling operations;
[0065] in, Figure 8 a in the middle is the water contact angle before 1000 bending and curling operations. Figure 8 (b) is the water contact angle after 1000 bending and curling operations.
[0066] Fig. 9 The water contact angle of the sample prepared in Example 5 before and after repeated adhesion and peeling of the 3M tape 100 times;
[0067] in, Fig. 9 a in the middle is the water contact angle before 100 times of repeated adhesion and peeling of 3M tape. Fig. 9 (b) is the water contact angle after 100 times of repeated adhesion and peeling of the 3M tape.
[0068] Fig.10 Relative fluorescence intensity and water contact angle of the sample prepared in Example 5 after being immersed in water for 240 hours;
[0069] The relative fluorescence intensity is relative to the fluorescence intensity of the sample before immersion in water, and 0 hour is recorded as 100%.
[0070] Fig.11 Relative fluorescence intensity and water contact angle of the sample prepared in Example 5 after 240 hours in a high temperature and high humidity environment (40°C, 80%);
[0071] The relative fluorescence intensity is the fluorescence intensity of the sample before the constant temperature and humidity treatment, and 0 hour is recorded as 100%.
[0072] Fig.12 Comparison of water contact angles of the sample prepared in Comparative Example 1 before and after being adhered with 3M tape once;
[0073] in, Fig.12 a is the water contact angle before adhesion, Fig.12 b in the figure is the water contact angle after adhesion.
[0074] Fig.13 is the light transmittance of the sample prepared in Comparative Example 2.
[0075] Fig.14 is the relative fluorescence intensity of the sample prepared in Comparative Example 3 after being immersed in water for 240 hours;
[0076] The relative fluorescence intensity is relative to the fluorescence intensity of the sample before immersion in water, and 0 hour is recorded as 100%.
[0077] Fig.15is the relative fluorescence intensity of the sample prepared in Comparative Example 3 after 240 hours in a high temperature and high humidity environment (40°C, 80%);
[0078] The relative fluorescence intensity is the fluorescence intensity of the sample before the constant temperature and humidity treatment, and 0 hour is recorded as 100%. DETAILED DESCRIPTION
[0079] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0080] In addition, unless otherwise specified, the raw materials used in the present invention can be obtained commercially, and any range recorded in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0081] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0082] The PDMS adhesives used in the embodiments and comparative examples of the present invention are all commercially available DOWSIL (Dow Corning) SYLGARD184 PDMS products, and are used in a mass ratio of PDMS main agent to curing agent of 10:1.
[0083] Example 1
[0084] Preparation of light conversion coating solution: Preparation of a spinach leaf-based solid-phase red light emitting carbon dot solution, the specific implementation steps are as follows:
[0085] Weigh 10 g of spinach leaves, wash them, dry them, grind them with a mortar, and soak and extract them with 40 mL of ethanol, then add 1 g of polyethylene glycol PEG-1000 to the extract, and perform ultrasonic treatment to completely dissolve the polymer; transfer the obtained mixed raw material solution to a high-pressure reactor, react at 150° C. for 7 hours, and naturally cool to room temperature after the reaction to obtain a crude product; centrifuge the obtained crude product at 10,000 rpm for 10 minutes to remove large particles, collect the supernatant as the final product, and place it in a 4° C. refrigerator for standby use.
[0086] 200 μL of the prepared PEG-modified carbon dot solution was transferred and diluted to 5 mL with ethanol. The excitation spectrum was measured by FLS1000 transient / steady-state fluorescence spectrometer to be 330-410 nm, and the emission range was 650-750 nm for red light, indicating that it can effectively absorb ultraviolet light and emit red light, and has excellent light conversion performance. After the carbon dot solution was dried, it was tested that it still had high photoluminescence performance in the solid state, indicating that the PEG-modified carbon dots have the properties of anti-aggregation quenching and solid-phase luminescence ( Figure 1 ).
[0087] Example 2
[0088] Preparation of light conversion coating solution: Preparation of a red light emitting carbon dot solution based on amaranth leaf base, the specific implementation steps are as follows:
[0089] Weigh 10 g of amaranth leaves, wash them, dry them, grind them with a mortar, and soak and extract them with 40 mL of ethanol, then add 0.5 g of polyvinyl pyrrolidone K30 to the extract, and perform ultrasonic treatment to completely dissolve the polymer; transfer the obtained mixed raw material solution to a high-pressure reactor, react at 160° C. for 10 hours, and naturally cool to room temperature after the reaction to obtain a crude product; centrifuge the obtained crude product at 10,000 rpm for 10 minutes to remove large particles, collect the supernatant as the final product, and place it in a 4° C. refrigerator for standby use.
[0090] Similarly, 200 μL of the prepared PVP-modified carbon dot solution was transferred and diluted to 5 mL with ethanol. The excitation spectrum was measured by FLS1000 transient / steady-state fluorescence spectrometer to be 330-410 nm, and the red light emission range was 650-750 nm, indicating that it also has the performance of ultraviolet absorption and red light emission. After the carbon dot solution was dried, it was tested that it also had high photoluminescence performance in the solid state, indicating that the carbon dots modified by PVP also have the performance of anti-aggregation quenching and solid-phase luminescence ( Figure 2 ).
[0091] Example 3
[0092] Preparation of light conversion coating solution: Preparation of a rapeseed leaf-based solid-phase red light emitting carbon dot solution, the specific implementation steps are as follows:
[0093] Weigh 10 g of rapeseed leaves, wash them, dry them, grind them with a mortar, and soak and extract them with 40 mL of ethanol. Then, add 1.5 g of polyethylene glycol PEG-600 to the extract and perform ultrasonic treatment to completely dissolve the polymer. Transfer the obtained mixed raw material solution to a high-pressure reactor, react at 180° C. for 6 hours, and naturally cool to room temperature after the reaction to obtain a crude product. Centrifuge the obtained crude product at 12,000 rpm for 12 minutes to remove large particles, collect the supernatant as the final product, and place it in a 4° C. refrigerator for standby use.
[0094] Example 4
[0095] Preparation of light conversion coating solution: Preparation of a red light emitting carbon dot solution of Setaria viridis leaf base solid phase, the specific implementation steps are as follows:
[0096] 10 g of Setaria viridis leaves were weighed, washed, dried, crushed with a mortar, and extracted by soaking with 40 mL of ethanol, and then 1 g of polyvinyl pyrrolidone PVP K60 was added to the extract, and ultrasonic treatment was performed to completely dissolve the polymer; the obtained mixed raw material solution was transferred to a high-pressure reactor, reacted at 120° C. for 24 hours, and naturally cooled to room temperature after the reaction to obtain a crude product; the obtained crude product was centrifuged at 12000 rpm for 15 minutes to remove large particles, and the supernatant was collected as the final product, which was placed in a 4° C. refrigerator for standby use.
[0097] Example 5
[0098] A method for preparing a light-converting, super-hydrophobic, self-cleaning composite coating on a polyethylene plastic film, the specific implementation steps are as follows:
[0099] 1) The polyethylene film was ultrasonically cleaned with water, ethanol and acetone for 10 minutes respectively, then dried with high-purity nitrogen, and then cleaned with oxygen plasma for 6 minutes before use;
[0100] 2) placing the prepared polyethylene film in the solid phase red light emitting carbon dot solution prepared in Example 1, soaking for 60 seconds, pulling once at a rate of 1 mm / s, pulling 15 times in total, and then drying at 40° C. for 2 hours to obtain a light conversion coating;
[0101] 3) placing the substrate with the light conversion coating in a solution of 40% by mass of a PDMS adhesive, soaking for 10 seconds, pulling it up once at a rate of 5 mm / s, pulling it up twice in total, and then heating it at 60° C. for 15 minutes to obtain a semi-cured adhesive coating;
[0102] 4) Finally, a super hydrophobic self-cleaning coating solution of n-hexane, PDMS adhesive, and hydrophobic silica in a mass ratio of 100:10:3 was ultrasonically treated for 30 minutes and then sprayed on the semi-cured adhesive coating at a spraying pressure of 0.3 MPa, a spraying distance of 15 cm, and a spraying time of 10 seconds. It was then placed at 60°C for curing for 2 hours to finally obtain a light-converting, super hydrophobic self-cleaning composite coating on a polyethylene film substrate.
[0103] Performance Testing
[0104] Figure 3The light transmittance comparison of the polyethylene film with the composite coating obtained in Example 5 and the polyethylene film without the composite coating (referred to as the original polyethylene film) shows that the light transmittance of the polyethylene film with the composite coating is only 2% lower than that of the original polyethylene film, indicating that the composite coating has good light transmittance. The inset is a digital photo of the original polyethylene film and the polyethylene film with the composite coating and their respective photos under 365nm ultraviolet light, indicating that the polyethylene film with the composite coating maintains the same light transmittance as the original film and has good red light emission performance.
[0105] Figure 4 Figures a and b are respectively the cross-sectional layer structure of the polyethylene film with the composite coating obtained in Example 5 and the rough structure diagram of the composite coating surface tested by a scanning electron microscope S-4800. Figure 4 The cross-sectional layer structure of a shows that the thickness of the selected polyethylene substrate is 85 μm, the prepared composite coating is evenly distributed on both sides of the substrate, and the total thickness of the single-side composite coating is 25 μm; Figure 4 Figure b shows that the sprayed superhydrophobic self-cleaning coating is tightly combined with the intermediate adhesion layer and forms a rough micro-nano structure, which is conducive to the formation of a superhydrophobic surface.
[0106] Figure 5 The fluorescence excitation and emission spectra of the polyethylene film with the composite coating of Example 5 were tested using the FLS1000 transient / steady-state fluorescence spectrometer. The results showed that the film had high ultraviolet absorption performance and high fluorescence emission at 650-750 nm.
[0107] Figure 6 The solar radiation intensity of the original polyethylene film and the polyethylene film with the composite coating of Example 5 was tested under sunlight using a handheld plant lighting spectrum detector UPRtek PG-200N, indicating that the composite coating has good light conversion performance.
[0108] Figure 7 Figures a and b show that the light-converting, superhydrophobic, self-cleaning composite coating has a water contact angle of up to 174° and a sliding angle of less than 2°.
[0109] Figure 8 In the figure, a and b are the water contact angles of the prepared composite coating before and after 1000 bending and curling operations (both greater than 160°), indicating that it has excellent superhydrophobic mechanical stability.
[0110] Fig. 9 In the figure, a and b are the water contact angles of the prepared composite coating before and after 100 repeated adhesions of 3M tape (both greater than 160°), which further illustrates that the composite coating has excellent superhydrophobic mechanical stability.
[0111] The polyethylene film with the composite coating of Example 5 was immersed in water to simulate rainy weather in a natural environment, and the light attenuation resistance and superhydrophobic stability of the polyethylene film with the composite coating were studied; Fig.10 It was shown that the composite coating still maintained 90% of the fluorescence emission intensity and excellent superhydrophobicity WCA>160° after being immersed in water for 240 hours.
[0112] The stability of the polyethylene film with the composite coating in a high temperature and high humidity environment was simulated by placing the polyethylene film with the composite coating in Example 5 in a constant temperature and humidity chamber at 40°C and 80% humidity; Fig.11 It shows that after 240 hours, the composite coating still maintains more than 90% of the fluorescence emission intensity and superhydrophobicity WCA>160°.
[0113] Example 6
[0114] A method for preparing a light-converting, super-hydrophobic, self-cleaning composite coating on a commercially available glass substrate, the specific implementation steps are as follows:
[0115] 1) The glass substrate was ultrasonically cleaned with water, ethanol and acetone for 10 minutes respectively, then dried with high-purity nitrogen, and then cleaned with oxygen plasma for 10 minutes before use;
[0116] 2) placing the prepared glass substrate in the solid-phase red light emitting carbon dot solution prepared in Example 2, soaking for 30 seconds, pulling once at a rate of 1 mm / s, pulling 10 times in total, and then drying at 40° C. for 2 hours to obtain a light conversion coating;
[0117] 3) placing the substrate with the light conversion layer in a solution of 50% by mass of a PDMS adhesive, soaking for 30 seconds, pulling it up once at a rate of 5 mm / s, pulling it up twice in total, and then heating it at 60° C. for 20 minutes to obtain a semi-cured adhesive coating;
[0118] 4) Finally, a super hydrophobic self-cleaning coating solution of n-hexane, PDMS adhesive, and hydrophobic silica in a mass ratio of 100:15:5 was ultrasonically treated for 30 minutes and then sprayed on the semi-cured adhesive coating at a spraying pressure of 0.25 MPa, a spraying distance of 15 cm, and a spraying time of 15 seconds. The coating was dried and cured at 60°C for 2 hours to finally obtain a light-converting, super hydrophobic self-cleaning composite coating on a glass substrate.
[0119] Comparative Example 1
[0120] After the polyethylene substrate is lifted and the light-converting coating is directly sprayed with the super-hydrophobic self-cleaning coating, the specific implementation steps are as follows:
[0121] 1) The polyethylene film was cleaned with water and ethanol for 10 minutes by ultrasonic cleaning, then dried with high-purity nitrogen, and then cleaned with oxygen plasma for 10 minutes before use;
[0122] 2) placing the prepared polyethylene film in the solid phase red light emitting carbon dot solution prepared in Example 1, soaking for 60 seconds, pulling once at a rate of 1 mm / s, pulling 15 times in total, and then drying at 40° C. for 2 hours to obtain a light conversion coating;
[0123] 3) Then, a super hydrophobic self-cleaning coating solution of n-hexane, PDMS adhesive, and hydrophobic white carbon black in a mass ratio of 100:15:5 was ultrasonically treated for 30 minutes and then directly sprayed on a polyethylene film with a light conversion layer. The spraying pressure was 0.3 MPa, the spraying distance was 15 cm, the spraying time was 10 s, and the film was dried and cured at 60 ° C for 2 hours to obtain a light conversion, super hydrophobic self-cleaning composite coating on the polyethylene film.
[0124] Performance Testing
[0125] After testing, the sample prepared in Comparative Example 1 has comparable fluorescence emission performance compared with the polyethylene film with light-converting, super-hydrophobic self-cleaning composite coating prepared in Example 5; however, the super-hydrophobic self-cleaning layer prepared by this method is very unstable compared with the super-hydrophobic self-cleaning layer in Example 5, and falls off after being adhered once by 3M tape, resulting in the disappearance of super-hydrophobic performance, see Fig.12 The results showed that after being adhered once with 3M tape, its water contact angle dropped from the super-hydrophobic 156° to 71°, which was similar to the original polyethylene film, indicating that the sprayed super-hydrophobic layer had been completely adhered away.
[0126] Comparative Example 2
[0127] 1) The polyethylene film was ultrasonically cleaned with water, ethanol and acetone for 10 minutes respectively, then dried with high-purity nitrogen, and then cleaned with oxygen plasma for 6 minutes before use;
[0128] 2) placing the prepared polyethylene film in the solid phase red light emitting carbon dot solution prepared in Example 1, soaking for 60 seconds, pulling once at a rate of 1 mm / s, pulling 15 times in total, and then drying at 40° C. for 2 hours to obtain a light conversion coating;
[0129] 3) placing the substrate with the light conversion coating in a solution of 40% by mass of a PDMS adhesive, soaking for 10 seconds, pulling it up once at a rate of 5 mm / s, pulling it up twice in total, and then heating it at 60° C. for 15 minutes to obtain a semi-cured adhesive coating;
[0130] 4) Finally, a super hydrophobic self-cleaning coating solution of n-hexane, PDMS adhesive, and hydrophobic silica in a mass ratio of 100:10:3 was ultrasonically treated for 30 minutes, and then pulled on the semi-cured adhesive coating. The solution was soaked for 10 seconds and pulled once at a speed of 5 mm / s, and then cured at 60°C for 2 hours to finally obtain a light-converting, super hydrophobic self-cleaning composite coating on a polyethylene film substrate.
[0131] Performance Testing
[0132] According to the light transmittance test, the sample prepared in Comparative Example 2 has a light transmittance of only about 20% (eg Fig.13 ), which is much lower than the original polyethylene film and cannot meet the practical application.
[0133] Comparative Example 3
[0134] A physically pressed composite film of a polyethylene film having a light-converting coating and a PDMS layer having a super-hydrophobic self-cleaning coating, the specific steps are as follows:
[0135] 1) The polyethylene film was ultrasonically cleaned with water, ethanol and acetone for 10 minutes respectively, then dried with high-purity nitrogen, and then cleaned with oxygen plasma for 6 minutes before use;
[0136] 2) placing the prepared polyethylene film in the solid phase red light emitting carbon dot solution prepared in Example 1, soaking for 60 seconds, pulling once at a rate of 1 mm / s, pulling 15 times in total, and then drying at 40° C. for 2 hours to obtain a polyethylene film with a light conversion coating;
[0137] 3) placing another new polyethylene substrate in a solution containing 60% PDMS adhesive by mass, soaking for 30 seconds, pulling it up once at a rate of 1 mm / s, pulling it up twice in total, and then heating it at 60°C for 15 minutes to obtain a semi-cured adhesive coating;
[0138] 4) Finally, a super hydrophobic self-cleaning coating solution of n-hexane, PDMS adhesive, and hydrophobic silica in a mass ratio of 100:10:3 was ultrasonically treated for 30 minutes and then sprayed on the semi-cured adhesive coating at a spraying pressure of 0.3 MPa, a spraying distance of 15 cm, and a spraying time of 10 seconds. The solution was then cured at 60°C for 2 hours, and the cured super hydrophobic self-cleaning PDMS layer was peeled off on the polyethylene film substrate to finally obtain a super hydrophobic self-cleaning PDMS layer.
[0139] 5) The super-hydrophobic self-cleaning PDMS layer and the polyethylene film with the light-converting layer in step 2) are pressed for 12 hours under a weight of 10 kg to obtain a light-converting, super-hydrophobic self-cleaning composite polyethylene film.
[0140] Performance Testing
[0141] The sample prepared in Comparative Example 3 was immersed in water for testing. It was found that the sample was dispersed into two layers after being immersed in water, namely, a light-converting polyethylene layer and a super-hydrophobic PMDS layer. That is, the adhesion between the composite coatings after physical pressing was poor, and they would be stratified after being immersed in water. Similarly, after 240 hours of immersion in water, the fluorescence intensity of the composite film decreased by 50% compared with that before immersion (such as Fig.14 ), its resistance to fluorescence decay is significantly lower than that of the sample prepared in Example 5.
[0142] Similarly, the composite film prepared in the comparative example also had the phenomenon of composite coating delamination during the high temperature and high humidity treatment process, resulting in water vapor contacting the light conversion layer, and finally causing the fluorescence intensity of the composite film to drop to about 60% of that before the treatment after 240 hours of high temperature and high humidity treatment (such as Fig.15 ), and its stability under high temperature and high humidity is also significantly lower than that of the polyethylene film with light-converting, super-hydrophobic and self-cleaning composite coating prepared in Example 5.
[0143] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a composite coating with light conversion, super-hydrophobic and self-cleaning functions, characterized in that: The steps include: 1) Prepare the light-converting coating solution The green plants are washed and ground, extracted with ethanol at room temperature, an alcohol-soluble polymer is added to the extract and ultrasonic treatment is performed to obtain a mixed raw material solution; The mixed raw material solution is transferred to a high-pressure reactor, reacted at 120-200°C for 2-24 hours, centrifuged after the reaction, and the supernatant is collected and refrigerated at 0-5°C for later use; 2) Preparation of adhesive coating solution dispersing the PDMS adhesive in a diluent to obtain an adhesion coating solution; 3) Preparation of super hydrophobic self-cleaning coating solution Dispersing PDMS adhesive and hydrophobic silica in a diluent to obtain a super hydrophobic self-cleaning coating solution; 4) Preparation of light-converting coating The pretreated substrate is immersed in a light conversion coating solution, pulled, and then dried at 40-60° C. for 0.5-2 h to obtain a light conversion coating; Alternatively, the light conversion coating solution is coated on the pretreated substrate, and then dried at 40-60° C. for 0.5-2 h to obtain the light conversion coating; 5) Preparation of semi-cured adhesive coating The substrate with the light conversion coating is immersed in the adhesive coating solution, pulled, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating; Alternatively, the adhesive coating solution is coated on the substrate having the light-converting coating, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating; 6) Preparation of super hydrophobic self-cleaning coating The super-hydrophobic self-cleaning coating solution is sprayed on the semi-cured adhesive coating, and cured to obtain a composite coating with light-converting and super-hydrophobic self-cleaning functions.
2. The preparation method according to claim 1, characterized in that: The green plants include one or more of amaranth, spinach, chrysanthemum, radish leaves, rape, kale, fennel, lettuce, auricularia auricula, water spinach, shepherd's purse, celery, ginkgo leaves, cypress leaves, clover, purslane, foxtail grass, morning glory leaves and Stephania truncatum; The alcohol-soluble polymer includes polyethylene glycol and / or polyvinyl pyrrolidone.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the green plants to the alcohol-soluble polymer is 10-20:
1.
4. The preparation method according to claim 1, characterized in that: The concentration of the PDMS binder in the adhesion coating solution is 20-60wt%; Preferably, the PDMS adhesive is selected from DOWSIL SYLGARD 184PDMS; Preferably, the diluent comprises one or more of n-hexane, petroleum ether, ethyl acetate and toluene.
5. The preparation method according to claim 1, characterized in that: In the super hydrophobic self-cleaning coating solution, the mass ratio of the PDMS adhesive, the hydrophobic white carbon black and the diluent is 0.02-0.2:0.01-0.1:
1.
6. The preparation method according to claim 1, characterized in that: Step 4 The specific steps of the lifting process are: The pretreated substrate is placed in the light-converting coating solution, and after soaking for 10-90 seconds, it is pulled once at a rate of 0.5-5 mm / s, for a total of 1-20 times, and then dried at 40-60° C. for 0.5-2 hours to obtain a light-converting coating.
7. The preparation method according to claim 1, characterized in that: Step 5 The specific steps of the lifting process are: The substrate with the light-converting coating is immersed in the adhesive coating solution, and after each immersion for 10-90 seconds, it is pulled once at a rate of 0.5-5 mm / s, and pulled 1-20 times in total, and then heated at 50-60° C. for 5-30 minutes to obtain a semi-cured adhesive coating; Preferably, in step 6, the spraying pressure is 0.1-0.3 MPa, the spraying distance is 10-25 cm, and the spraying time is 3-15 s; Preferably, in step 6, the curing temperature is 50-60° C. and the curing time is 0.5-2 h.
8. The preparation method according to claim 1, characterized in that: The substrate includes plastic agricultural film, architectural glass or photovoltaic glass.
9. A composite coating with light-converting, super-hydrophobic and self-cleaning functions, characterized in that: The method is described in any one of claims 1 to 8.
10. Use of the composite coating according to claim 9 in the preparation of agricultural greenhouses, building materials, and solar cells.
Citation Information
Patent Citations
Functional carbon dots, and preparation and application thereof
CN103160279A
Highly-wear-resistant super-hydrophobic composite coating and preparation method thereof
CN105419450A
Application of carbon dots in light conversion of agricultural production as agricultural light conversion material
CN106590640A
Super-hydrophobic self-cleaning coating and preparation method thereof
CN111647290A
Improvements relating to superhydrophobic surfaces
US20220145084A1
Cited By
Organic-inorganic hybrid fluoride-free antifouling self-cleaning resin as well as preparation and application thereof
CN120574399A
